Participation in network marketing companies :the motivational factors that influence the part-time distributors in Kuching, Sarawak - Ng, Gek Keun (Universiti Malaysia Sarawak, 2004)
The main aim of this is to study is to determine whether there are significant relationship between the respondents' decision making becoming distributors in network marketing companies and the four motivational factors (financial satisfaction flexibility, job satisfaction and social satisfaction)